Unveiling the determinant factors of go club program loyalty in a super application - Sundjaja, Arta M; Andysa, Shavira; Suryapranata, Remigius AP; Pratama, Naufal R; Colline, Fredella (International Journal of Management and Sustainability, 2024)
This research aimed to analyze the factors affecting super application brand loyalty with the emergence of digital loyalty programs in Indonesia. A strong super-application has gained popularity and sustained customer demand due to Indonesia’s smartphone industry expansion. To achieve this objective, a quantitative-qualitative approach utilizing Structured Equation Modeling (SEM) and interviews was employed. Ten-fold indicators determined the sample size, while convenience sampling gathered 392 respondents. The software for data analysis is SmartPLS 4.1.0.0. The results indicate the acceptance of eight hypotheses and the rejection of the remaining two. Playfulness is positively affecting attitudes and loyalty program usage. Next, affective commitment positively affects attitude and loyalty program usage. Next, reward attractiveness positively affects attitude. Finally, the relationship between attitude, usage, satisfaction, and loyalty is significant. The determinant factors of brand loyalty were playfulness, reward attractiveness, and affective commitment. The theoretical contribution is that the impact of loyalty programs on brand loyalty reveals that factors like playfulness and affective commitment influence attitudes and usage, despite gamification’s potential moderating effect. The practical implication is that Gojek should improve its loyalty program strategy by diversifying the range of rewards and integrating gamification, particularly in-app games, to maintain user engagement and brand loyalty.